What do medical students think of own participation as subjects in clinical trials? - Sič, Aleksandar; Gazibara, Tatjana (Journal of Evaluation in Clinical Practice, 2024)
Rationale and Aim: Testing of new drugs through clinical trials is essential in efforts to increase generalizable knowledge. Little is known about the medical students' perception of their participation as research subjects in clinical trials. The aim of this study was to examine the willingness and attitudes of medical students towards participation as volunteer subjects in clinical trials. Methods: A cross‐sectional study was conducted among 297 medical students in years 4, 5 and 6 at the University of Belgrade, from October to December 2023. Participants completed a pen‐and‐paper questionnaire including demographic characteristics, opinions on their participation in clinical trials, and attitudes towards clinical trials in general. The validity of the attitude scale was verified. Results: One in five medical students expressed a positive opinion about their participation in clinical trials, with the majority (about one‐half) remaining undecided. General attitudes of students about research and their participation were positive. Students with prior blood donation experience were more willing to participate. Lower socioeconomic status and volunteering experience were also associated with stronger positive attitudes towards clinical trials in general. Conclusion: Most students were undecided about their participation, but their attitudes towards clinical trials in general were positive. Positive attitudes towards clinical trials did not uniformly translate to the willingness for personal participation. Promotion of blood donation and volunteering at universities could help to increase the interest in clinical trials as volunteer subjects.